Análise do conhecimento, sobre Leishmaniose Visceral e outras zoonoses, de docentes dos três primeiros anos do ensino fundamental em escolas da região noroeste de Belo Horizonte, Minas Gerais, 2008. - Leticia Mendonca Lopes Ribeiro (2010)
Zoonoses are diseases manifested by animals and transmissible to humans, as well as those transmitted from animals to man. An important example of zoonosis is visceral leishmaniasis, serious illness that presents a complex control, assuming the need for social and politicalfactors are involved, such as the work can involve elementary school teachers on issues of health education. The city of Belo Horizonte was chosen for the study because of the prevalence of human and canine cases of the disease. The Northwest of the city was chosen for the limit of the research because of the impact with that visceral leishmaniasis is treated in this area and the great acceptance of the proposal by the Regional Northwest that work with the disease control. The research aimed to analyze the knowledge that primary school teachershave on zoonoses, especially visceral leishmaniasis, as well as the representation given by these professionals to approach the subject in four private and four public institutions located in the northwest region of Belo Horizonte/MG. The teachers, who taught for the first three years ofprimary education in the participating schools were interviewed, totaling 40 teachers - 16 in private schools and 24 in public. Was use of semistructured interviews, and all interviews were recorded and the information given by respondents were recorded. Qualitative demonstrations were done, but quantitative demonstration was used to emphasize certain results. The material was analyzed using the technique of discourse analysis. The questions had the support of thetheory of social representations for better understanding. The interviewees seem to have little familiarity with the practice of school theme zoonoses, not being observed the same practice inmatters related to dengue. In relation to visceral leishmaniasis, the character (private or public) of the institution where the teachers interviewed were not found to influence acquisition ofknowledge about the disease by the interviewees, since most of the information taken by these professionals on the subject is linked to their personal experiences. Most of the interviewees faces the euthanasia of dogs positive for visceral leishmaniasis as a necessary alternative tothe impossibility / impracticability of treatment canine. Most of the interviewees, who owned dogs, credits the control of zoonoses great responsibility and skill in developing diagnostics and control of visceral leishmaniasis in dogs. Considerable proportion of teachers trust theirstudents how important multipliers of information on visceral leishmaniasis and other animal diseases, illustrating the homework already consolidated with dengue to support that credibility.It is suggested that new proposals on the theme zoonoses can be developed and school projects that are more concise set out to approach the subject in the early years of elementary school, which will enable the strengthening of prevention and control of visceral leishmaniasisand other zoonoses.